A Unique Case of Unilateral Lower Extremity Sparing Systemic Peripheral Gangrene. (13th December 2012) - Markelov, Alexey; DeFroda, Steven; Baccaro, Leopoldo; Bastidas, Jamie
Abstract : We present here the case of a 70-year-old female who developed a systemic peripheral gangrene in both of her upper extremities (all fingers) and her right foot due to a severe septic shock requiring a systemic vasopressor therapy. Interestingly, the patient's left foot remained spared from gangrenous changes possibly due to a chronic external iliac artery occlusion and thus the lower concentration of vasopressors in that extremity.